Comparison of Auditory Intellectually Repetition Approach and Student Teams Achievement Division Approach to Mathematics Learning Outcomes of Elementary School Students - Abdul, Karim; Rukli, Rukli; Sukmawati, Sukmawati (Institut Agama Islam Negeri Palopo, 2022)
This study compares the Auditory Intellectually Repetition approach and the Student Teams Achievement Division approach to elementary school mathematics learning outcomes. This type of research is quantitative research. The research design used is the Pretest Posttest Control Group Design. The population in this study were fifth-grade students in Mappkasunggu District, and the samples of this research were fifth-grade students of public elementary school No. 106 Inpres Takalar I and fifth-grade students of state elementary school no. 23 Center Takalar I. The data collection technique used was multiple choice questions. The research results based on descriptive analysis showed that the average value of mathematics learning outcomes with the AIR learning approach reached 75.33, and the Student Teams Achievement Division approach reached 60.67. At the same time, the results of the inferential analysis show that the Auditory Intellectually Repetition approach has a more significant effect than the Student Teams Achievement Division approach on student mathematics learning outcomes. The sig value obtained based on the multivariate test table in the Manova test is smaller than 0.05.